2022
DOI: 10.3390/jcm11154308
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Reasons for Nonadherence to Medication in Adults with Epilepsy: A Review of Self-Report Measures and Key Predictors

Abstract: This review presents individual reasons for self-reported nonadherence in people with epilepsy (PWE). A literature search was performed on the PubMed/Medline and Scopus databases for studies published up to March 2022. Thirty-six studies were included using the following inclusion criteria: original studies on adults with epilepsy, use of subjective self-report adherence measurement methods, and publication in English. Data were extracted using a standardized data extraction table, including the year of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
(371 reference statements)
4
9
1
Order By: Relevance
“…A prevalence of 39 % non-adherence is lower than what has been described in many studies, and lower than the estimated average of 50 % in studies on self-reported adherence in the systematic review by Mendorf et al [10] . It is difficult to compare the statistics between studies, due to the extensive methodological variations.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A prevalence of 39 % non-adherence is lower than what has been described in many studies, and lower than the estimated average of 50 % in studies on self-reported adherence in the systematic review by Mendorf et al [10] . It is difficult to compare the statistics between studies, due to the extensive methodological variations.…”
Section: Discussioncontrasting
confidence: 56%
“…Sub-optimal adherence is common in people with epilepsy (PWE), but the prevalence varies largely between studies depending on the used methods and definitions of adherence. A review published in 2017 found sub-optimal adherence in 26–79 % of patients in 17 studies [9] , and a systematic review published in 2022 on studies using different self-report measures for adherence found rates of sub-optimal adherence between 21 and 95 % in 36 studies, with an estimated average rate of almost 50 % [10] . The most commonly mentioned self-reported reason for non-adherence in the latter review was forgetfulness.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study in Brazilian patients with epilepsy, forgetfulness was also a major factor responsible for non-adherence. Another important factor was the adverse effects of the anti-epileptic drugs taken [ 28 , 36 , 37 ]. To minimize the risk of skipping a dose, it is recommended to use pill organizers, taking medication during meals and using reminder mobile applications [ 12 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s personal thoughts about the need to take the medicine, the benefits of taking it, and the concerns about possible side effects and costs associated with taking the drug often determine the level of compliance with medical recommendations [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Reasons for nonadherence are often complex and multilayered, ranging from forgetfulness to concerns about medication side effects, lifestyle factors, or financial constraints. [5][6][7] Estimates indicate that 25%-75% of adults with epilepsy may not optimally adhere to their ASM regimen. 4,6,8,9 Challenges arise in clinical decision-making when patients fail to communicate missed doses or misremember them, 10,11 potentially resulting in unwarranted medication regimen alterations.…”
Section: Introductionmentioning
confidence: 99%